The Influence of Microteaching Effectiveness on Teaching Skills and Readiness: A Study of Islamic Education Students - Mufid, Muhammad; Li’illiyyina, Irfa Ma’alina (TA'DIBUNA: Jurnal Pendidikan Agama Islam, 2024)
Teaching skills are not limited to the delivery of lesson material but the complexity of the demands of learning outcomes. The purpose of this study is to reveal the relationship between the effectiveness of microteaching implementation with teaching skills and teaching readiness of Islamic Education Study Program students of UIN K.H. Abdurrahman Wahid Pekalongan. This study used a survey research method with a quantitative research approach focused on revealing causal relationships and testing hypotheses. The population in the study was Islamic Education students who had taken microteaching courses. Identification with probability sampling technique using the Slovin formula is 74 students. Path analysis was used through a regression approach and using AMOS software version 24.0. The calculation results obtained that the effectiveness of microteaching courses with a path coefficient value = 0.575 has a positive effect on teaching skills, while microteaching courses with teaching readiness does not have a positive effect with a path value = 0.244. While teaching skills with teaching readiness there is a positive influence of 0.621. from the results of the above research, the implementation of controlled microteaching can develop students' skills, but in teaching readiness, identifying is influenced by other factors such as infrastructure, motivation, teaching techniques, pedagogical knowledge, and self-confidence, from the importance of constructive feedback in microteaching sessions.